Determinants of Brand Equity: The Roles of Brand Awareness, Association, Loyalty, and Image in the Airline Industry - Kok Ban Teoh; Kia Hui Gan; Foong Jia Yee; Gan Lee Fan; Lin Shihui; Fathimah Az-Zahra Binti Harudin; Fu Wei; Anees Jane Ali; Daisy Mui Hung Kee (International Journal of Tourism and Hospitality in Asia Pasific, 2025)
AirAsia, a Malaysian low-cost airline, has recently faced operational challenges such as customer complaints, IT disruptions, and flight delays that have weakened customer trust and loyalty, leading to a decline in its overall brand equity. This study aims to examine the key factors influencing AirAsia’s brand equity, focusing on four independent variables: brand awareness, brand association, brand loyalty, and brand image. A total of 151 respondents participated in an online survey distributed via Google Forms, and the collected data were analyzed using descriptive and regression analysis through SPSS. The findings reveal that brand awareness (? = 0.260, p 0.01) and brand image (? = 0.394, p 0.001) significantly and positively influence brand equity, while brand association (? = 0.146) and brand loyalty (? = 0.104) have positive but insignificant effects. The model explains 69.6% of the variance in brand equity (R² = 0.696). These results suggest that AirAsia should strengthen brand awareness through digital marketing and improve brand image by enhancing customer experience, reliability, and communication to foster stronger brand equity.